Corruption victimization and anti‐incumbent voting. Issue 4 (30th November 2021) - Bourassa, Aimée; Weitz‐Shapiro, Rebecca; Winters, Matthew S.
Abstract: Do citizens punish elected politicians for corruption carried out by unelected bureaucrats? Most studies of corruption punishment focus on accusations against politicians. We argue that the direct, and therefore undeniable, experience of corruption at the hands of street‐level bureaucrats will lead citizens to punish national incumbents. We explore whether this punishment of corruption is mitigated in circumstances where voters believe that politicians have less control over bureaucrats. We combine cross‐national survey data on corruption victimization and political behavior in a sample of 60 countries from Africa and Latin America. We find a robust, negative effect of personal corruption victimization on vote intention. Surprisingly, we do not identify any significant country‐level predictors of the strength of this relationship, nor do we find evidence of systematic differences in how copartisans respond to bureaucratic corruption relative to noncopartisans. Our paper contributes to the growing literature on how interaction with street‐level bureaucrats drives political behavior.